Pengaruh Pembelajaran Digital terhadap Motivasi Belajar dan Hasil Belajar Siswa di Era Pandemi Covid-19 - Efvinggo Fasya Jaya SP (Edunusa: Journal of Economics and Business Education, 2022)
The use of digital technology in learning is certainly necessary, especially if you look at the current world conditions that are being hit by the Covid-19 pandemic. The Covid-19 pandemic is arguably the relevance that drives the acceleration of digital learning. Departing from this, the purpose of this research is 1) to find out how the influence of digital learning on students' learning motivation 2) to find out how the influence of digital learning on student learning outcomes. This research is a descriptive quantitative study with a population of all students of class XI majoring in Social Sciences (IPS) 4th High School Yogyakarta. Based on the analysis conducted, this study found that digital learning (X) had an effect on students' learning motivation (Y1) by 76.3% while the remaining 23.7% learning motivation (Y1) was influenced by other variables outside the study with a significant value. 0.000 <0.05 and the t-test value obtained a t-count value of 16.463 > 1.992 t table. Then, digital learning (X) affects the learning outcomes (Y2) of students by 70.1% while the remaining 29.9% learning outcomes (Y2) are influenced by other variables outside the study with a significance value of 0.000 <0.05 and the test value t found the result that t count 14,029 > 1,992 t table. These results are due to the fact that digital learning has many variations and features that can be utilized, in addition to flexibility which is also able to help students learn anytime and anywhere.